Pengaruh Volume Minyak Sumbawa Sebagai Antibakteri dalam Pembuatan Sabun Mandi Cair - Muhamad Zaenudin; Ahmadi Ahmadi; Hulyadi Hulyadi (Hydrogen: Jurnal Kependidikan Kimia, 2020)
Soap is a necessity for daily life, such as for bathing, washing, and cleaning other necessities. Normally various kinds of bacteria and fungi can live permanently on the skin, for example, such as thebacteria Staphyloccocus aureus. Antibacterial soap is used as a solution to this bacterial problem. Sumbawa oil is a natural ingredient that has the potential to be antibacterial in body wash. Sumbawa oil contains geraniol and citronellal, flavonoids, polyphenols and also contains saponins and tannins. The research objective was to find out what volume of Sumbawa oil is used to obtain the quality of liquid bath soap which has antibacterial content and meets SNI standards. This research is an experimental research in a laboratory by varying the volume of Sumbawa oil. The parameters measured in this study were the effect of variations in the volume of Sumbawa oil on antibacterial properties and pH of liquid bath soap. The findings in this study that the best antibacterial properties were found in the addition of 15 ml volume of Sumbawa oil with an average inhibition zone of 19.5-22.3 mm and a pH of 5 ml of Sumbawa oil volume with an average pH of 6.1. Based on the above findings, it can be concluded that the addition of Sumbawa oil has an effect on the antibacterial properties and pH of liquid bath soap.